2018
DOI: 10.1111/jcpp.12896
|View full text |Cite
|
Sign up to set email alerts
|

Do clinical characteristics predict the cognitive course in early‐onset schizophrenia‐spectrum disorders?

Abstract: Though at different levels, the EOS group and the controls had a similar cognitive course over 2 years. Some baseline characteristics (psychotic symptoms, DUP, remission, and hospitalization) had no influence on cognition within the first 2 years of illness. In contrast, general symptoms and a history of suicide attempts at baseline were more potent risk factors of the cognitive course than the psychotic-specific symptoms, and should, therefore, be subject to specific attention in the evaluation and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Our own research group similarly found significant cognitive improvement across the acute phase of psychosis (30). A recent 24-month longitudinal study of young people with early onset schizophrenia also found this group to have a similar cognitive course to healthy controls, albeit functioning at an overall lower level (31). Improvement has also been seen in first episode schizophrenia, even with test batteries designed to withstand learning effects (32).…”
Section: Introductionmentioning
confidence: 89%
“…Our own research group similarly found significant cognitive improvement across the acute phase of psychosis (30). A recent 24-month longitudinal study of young people with early onset schizophrenia also found this group to have a similar cognitive course to healthy controls, albeit functioning at an overall lower level (31). Improvement has also been seen in first episode schizophrenia, even with test batteries designed to withstand learning effects (32).…”
Section: Introductionmentioning
confidence: 89%
“…Neurocognitive data from the Early-Onset Study have been published in previous papers, e.g. [ 15 , 18 , 42 ]. The inclusion criteria in both cohorts were: (1) Non-affective early-onset psychosis (schizophrenia, schizoaffective disorder, schizophreniform disorder, psychotic disorder not otherwise specified, brief psychotic disorder), according to the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV), (2) age between 12 and 18 years, (3) written informed consent obtained from participants, parents or guardians (if the participant was under 16 years), (4) language abilities to complete the interviews and self-rating questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…In a review of cross-sectional studies of neuropsychological functioning in individuals with EOS, Frangou (2010) found impairments of medium to large effect sizes in IQ, attention, memory and executive functions compared with TD controls. One-year and two-year longitudinal studies of neuropsychological impairments in EOS found no change in the magnitude of deficits in patients with EOS (Cervellione, Burdick, Cottone, Rhinewine, & Kumra, 2007;Juuhl-Langseth, Holmen, Thormodsen, Oie, & Rund, 2014;Teigset et al, 2018). In two studies featuring four-year and 13-year follow-up intervals, there was a decline in verbal memory, attention and processing speed in individuals with EOS (Frangou, Hadjulis, & Vourdas, 2008;Oie et al, 2011;Wozniak, Block, White, Jensen, & Schulz, 2008).…”
Section: Introductionmentioning
confidence: 95%